2016
DOI: 10.1038/srep22814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute intra-abdominal hypertension on multiple intestinal barrier functions in rats

Abstract: Intra-abdominal hypertension (IAH) is a common and serious complication in critically ill patients for which there is no well-defined treatment strategy. Here, we explored the effect of IAH on multiple intestinal barriers and discussed whether the alteration in microflora provides clues to guide the rational therapeutic treatment of intestinal barriers during IAH. Using a rat model, we analysed the expression of tight junction proteins (TJs), mucins, chemotactic factors, and Toll-like receptor 4 (TLR4) by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
0
37
1
Order By: Relevance
“…24 We found that as the IAP increases to 20 mm Hg for 90 min, intestinal barriers become seriously disrupted and dysbiosis occurs. 25 However, in the present study, at the same level of IAH, MICU1 exhibited a compensatory response towards the increased intestinal permeability, indicating that under IAH, the gut promotes a self-protective mechanism. Further studies would be needed to establish whether MICU1 would be disrupted as the course/degree of IAH progresses, and to determine what roles are played by MICU1 in the subsequent abdominal compartment syndrome and gut-derived sepsis.…”
Section: Discussioncontrasting
confidence: 62%
“…24 We found that as the IAP increases to 20 mm Hg for 90 min, intestinal barriers become seriously disrupted and dysbiosis occurs. 25 However, in the present study, at the same level of IAH, MICU1 exhibited a compensatory response towards the increased intestinal permeability, indicating that under IAH, the gut promotes a self-protective mechanism. Further studies would be needed to establish whether MICU1 would be disrupted as the course/degree of IAH progresses, and to determine what roles are played by MICU1 in the subsequent abdominal compartment syndrome and gut-derived sepsis.…”
Section: Discussioncontrasting
confidence: 62%
“…This family is present in values lower than 1% in all other animals. However, its role here is difficult to determine due to the contradictory character assigned to this family in the literature, either as an actor in different pathologies [77,78] or as a keeper of the gut homeostasis [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…The scoring was performed independently by 3 dermatopathologists. The detailed scoring system was based on the reported literature (15).…”
Section: Immunohistochemistrymentioning
confidence: 99%